Perancangan Sistem Pendukung Keputusan Pemilihan Supplier dengan Metode AHP (Studi Kasus Toko Anugerah) - Teguh Khristianto; Hersatoto Listiyono (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Retail business involves transactions or direct sales of goods to consumers. In this context, the ability to understand consumer demand is crucial. Meeting consumer desires requires supplier involvement. Therefore, Anugerah uniform store requires a Decision Support System (DSS) that can assist in accurately selecting suppliers based on desired criteria. The supplier selection process is built using the Analytical Hierarchy Process (AHP), a method for ranking decision alternatifs and choosing the best one from multiple criteria. Criteria specified by Anugerah uniform store include price, distance, and quality.